Analysis of The Numerical Ability of Elementary School Students in Terms of The Introduction to Place Values of Numbers - Umar Umar; Arif Widodo (IKIP Siliwangi, 2021)
Recognizing place value is one of the basic skills in numeracy. Numerical ability can be seen through students' ability to recognize the place value of numbers. This study aims to analyze students' numeracy skills in terms of their ability to recognize place values in numbers. The research was conducted at one of the public elementary schools in the Central Lombok district. The type of research used is a descriptive survey. Data collection using tests. The instrument used is a place value test. The number of research samples was 110 elementary school students, with details of 53 low-grade students and 57 high-grade students. Data were analyzed using descriptive statistics. If viewed from the ability to recognize place values, students' numeracy abilities are included in the fairly good category. Overall out of 110 students 60% have recognized the place value of thousands. Most of the high-grade students already know the place value of the thousands, while the low-grade students are mostly still in the places value of units, tens, and hundreds. The number of students who know the value of the hundreds is 13%, the tens value is 16% and the unit value is 8%. The study also found fact that there were 3% of students were not familiar with numbers. Although overall students' numeracy skills are quite good, special attention needs to be given to high-grade students who are not able to recognize the place value of thousands and low-grade students who are not yet familiar with numbers.